2011
DOI: 10.1002/eji.201141758
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hedgehog signalling at the transition from double‐positive to single‐positive thymocyte

Abstract: In the thymus, developing T cells receive signals that determine lineage choice, specificity, MHC restriction and tolerance to self-antigen. One way in which thymocytes receive instruction is by secretion of Sonic hedgehog (Shh) from thymic epithelial cells. We have previously shown that Hedgehog (Hh) signalling in the thymus decreases the CD4:CD8 single-positive (SP) thymocyte ratio. Here, we present data indicating that double-positive (DP) thymocytes are Hh-responsive and that thymocyte-intrinsic Hh signall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
27
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 44 publications
10
27
1
Order By: Relevance
“…As our findings were in contrast to several other reports describing an influence of Hh signaling on the transition from the double-positive (DP) to the single-positive (SP) stage of thymocyte development [22], [23], [24], we decided to repeat the analyses with mice backcrossed to the C57BL/6 background. Although the overall thymic cellularity (Figure 1A) and the percentages of double-negative (DN) thymocytes (Figure 1B,C) were similar in both genotypes, we found that the relative number of DP thymocytes was increased in Ptch flox/flox CD4Cre +/− mutant mice while the percentages of CD4 and CD8 SP thymocytes were decreased (Figure 1C).…”
Section: Resultscontrasting
confidence: 74%
“…As our findings were in contrast to several other reports describing an influence of Hh signaling on the transition from the double-positive (DP) to the single-positive (SP) stage of thymocyte development [22], [23], [24], we decided to repeat the analyses with mice backcrossed to the C57BL/6 background. Although the overall thymic cellularity (Figure 1A) and the percentages of double-negative (DN) thymocytes (Figure 1B,C) were similar in both genotypes, we found that the relative number of DP thymocytes was increased in Ptch flox/flox CD4Cre +/− mutant mice while the percentages of CD4 and CD8 SP thymocytes were decreased (Figure 1C).…”
Section: Resultscontrasting
confidence: 74%
“…Neutralisation of Hh signals in FTOC by treatment with neutralising anti-Hh monoclonal antibody has previously been shown to promote T-cell development, and increase differentiation from CD3 hi DP to mature SP cell and to increase the CD4SP:CD8SP ratio [19, 20]. Hhip-treatment significantly increased the proportion of CD3 hi thymocytes in the WT FTOC, compared to control untreated cultures (Figure 4C-4D).…”
Section: Resultsmentioning
confidence: 90%
“…Data for the differentiation, proliferation, and survival of the earliest DN thymocyte subsets, the transition from DN to DP, as a negative regulator of pre-TCR-induced thymocyte expansion (79)(80)(81)(82)(83), the transition from DP to SP, for TCR repertoire selection, at the CD4/ CD8 lineage decision (84,85), and negative selection (83) all support a role for Hh signaling in T cell development. In contrast, other work showed that the Hh signal transducer Gli1 is not needed to mediate the effects of Hh signaling at early stages of thymocyte differentiation (86), and gain-and loss-of-function genetic models of Smoothened show that it is not required for adult BM HSC self-renewal or differentiation or for thymocyte development (87).…”
Section: Hh-signaling Pathwaymentioning
confidence: 99%